The concept of globalization: Contemporary approaches - Urbšienė, Laima (Business: Theory and Practice, 2011)
Although the notion of globalization is widely used in contemporary life, yet we lack its distinct and precise concept; there are still problems in terminology and in the overall consolidated theory of globalization itself. One of the reasons why there is no tightly focused full-length assessment of the main social processes creating the essence of globalization is the difference in social paradigms that scientists approach the issue of globalization with. The present paper analyses and compares different approaches of scientists representing different schools of economic mind; it provides the definition and description of globalization and compares it with the notion of internationalization and integration. Comparative analysis of the main theoretical concepts of globalization is done on the basis of individualistic and holistic paradigms and on the interpretation of globalization presented by the three main schools - globalism, skepticism, and transformationalism. The present article analyses and compares the concepts of globalization, principle statements, and thoughts about the essence of globalization developed by the above mentioned schools and their representatives, as well as their approach to the reasons and factors that have determined different stages of globalization. The main emphasis is laid on those aspects of globalization where their opinions and the evaluation of the processes of globalization are most significantly diverse. The author’s position is presented by way of defining the concept of globalization and systematizing the main factors of globalization, which create preconditions for the development of the processes of globalization and influence its consequent course.Article in Lithuanian.Globalizacijos samprata: šiuolaikiniai požiūriaiSantrauka. Nors plačiai vartojama globalizacijos sąvoka nėra galutinai konceptualizuota, išlieka terminologijos problemų, trūksta susistemintos globalizacijos teorijos. Viena priežasčių – skirtingas mokslininkų paradigminis požiūris, tad iki šiol nepasiekta sutarimo dėl jos esmę sudarančių socialinių procesų. Šiame darbe analizuojamas ir lyginamas įvairioms filosofinėms mokykloms atstovaujančių  ekonominės  minties  atstovų  požiūris  į  globalizaciją,  konceptualizuojama  globalizacijos  sąvoka,  ji  lyginama  su internacionalizacijos ir integracijos sąvokomis. Remiantis individualistine ir holistine paradigma bei trijų pagrindinių mokyklų – globalistų, skeptikų ir transformacionalistų globalizacijos traktavimu atliekama teorinių globalizacijos koncepcijų lyginamoji analizė. Straipsnyje analizuojamos ir lyginamos šių mokyklų bei joms atstovaujančių įvairių autorių suformuluotos globalizacijos sąvokos,  pagrindiniai  teiginiai  apie  globalizaciją,  globalizacijos  esmę,  priežastis  ir  veiksnius,  lėmusius  atskirus  globalizacijos etapus. Akcentuojami tie globalizacijos aspektai, dėl kurių jų požiūris ir globalizacijos procesų vertinimai kardinaliai išsiskiria. Autorės pozicija pateikiama apibrėžiant globalizacijos sąvoką ir susisteminant pagrindinius globalizacijos veiksnius, kurie sudaro prielaidas vystytis globalizacijos procesams ir daro įtaką tolesnei globalizacijos eigai.Reikšminiai žodžiai: globalizacija, individualistinė ir holistinė paradigma, globalistai, transformacionalistai, skeptikai, globalizacijos veiksniai, internacionalizacija, regionalizacija, integracija.